Tela’ah Kajian Aksiologi dalam Persepektif Islam dan Sains Modern - Alfi Farikhatul Ula; Muniron (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Axiology, as a branch of philosophy, means the knowledge that philosophically explores the 'values' inherent in something. This implies a critical, rational, and speculative examination. Axiology provides benefits in order to anticipate negative developments in human life. Broadly speaking, axiology is divided into two fields, namely ethics and aesthetics. The discussion of these two fields has different starting points between Islamic scholarship and modern Western science. In the construction of Islamic scholarship, knowledge operates within the framework of the Islamic paradigm, where knowledge directly derives from the Qur'an as a revelation text. In the Western historical context, the emergence of the Enlightenment period in the 17th century, which transformed into modernity, became a dividing line between science and religion in the West. This event is interpreted as a rebellion of humanity against God (Christianity), with modernity being the offspring of this rebellious spirit born from the Renaissance. Using a literary approach, this article explores insights by conducting a comparative analysis between the two perspectives. The result indicates that the starting point for ethics as a branch of philosophy is reason, not religion, while Islamic ethics is grounded in the Qur'an and hadith.